An evaluation of senior drivers performance in a simulated airport road access wayfinding - Anuar, Nur Khairiel (IP Publishing LLC, 2018)
Drivers prefer an effective airport wayfinding system in airport areas to navigate easily. In many cases, drivers experience most difficulties to understand a complete wayfinding process which stimulates a distraction while driving. The purpose of this study is to investigate the wayfinding and signage provisions, sensitivity of driving behavior and road safety. A driving simulator to simplify the airport navigation was developed. Three scenario types were designed to provide a variety of driving situations and complexity of the road designs to the airport. The complexity of wayfinding with the assorted road furniture such as signage adverts and street lights also were included. Experience car drivers who held valid UK driving license were asked to drive simulated routes. Fifteen drivers in range of age 50-54, 55-59 and over 60 years were selected to perform the study. Participants drove for approximately 20 minutes to complete the simulated driving. The types of errors (parameter) of simulated driving were identified: risk of collisions, exceed the speed limit, traffic light tickets, centerline crossings and road edge excursions. The drivers’ performance and parameter were compared to the age group. Results were analyzed by ANOVA and discussed with reference to the use of driving simulator.